O uso da simulação na determinação de planos de produção agrícola - dos Santos, Maurinho Luiz; Rodrigues, Lécio Maria; Coelho de Alvarenga, Sonia; Batista de Oliveira, Evonir (Revista Ceres, 2025)
Simulation is used in this work through and application of the model developed by Donaldson and Webster. Randon numbers were used in the selection process.